2021
DOI: 10.1093/rheumatology/keab247.063
|View full text |Cite
|
Sign up to set email alerts
|

P066 Telephone clinics: what are our patients saying?

Abstract: Background/Aims  Telemedicine has not previously been a regular part of routine rheumatology services.Our department adopted telephone clinics during the COVID-19 pandemic. We assessed patient satisfaction by conducting a feedback survey. Our aim was to obtain a patient perspective on remote consultations and on preferred future follow up options including video or face-to-face consultations. Methods  The cohort included 160 rheumatology patients who had a telephone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…18 This suggests a desire from patients to embrace this change, but there will always remain a clinical need to review patients in person. The availability nationwide of videoconferencing is only 36% 19 ; however, our study showed that telephone consultations alone are feasible and may not negatively impact patient outcomes. We are facing a climate crisis, with healthcare not only a significant contributor but also subsequently burdened by the negative health outcomes that result.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…18 This suggests a desire from patients to embrace this change, but there will always remain a clinical need to review patients in person. The availability nationwide of videoconferencing is only 36% 19 ; however, our study showed that telephone consultations alone are feasible and may not negatively impact patient outcomes. We are facing a climate crisis, with healthcare not only a significant contributor but also subsequently burdened by the negative health outcomes that result.…”
Section: Discussionmentioning
confidence: 64%
“…This suggests a desire from patients to embrace this change, but there will always remain a clinical need to review patients in person. The availability nationwide of videoconferencing is only 36%19; however, our study showed that telephone consultations alone are feasible and may not negatively impact patient outcomes.…”
Section: Discussionmentioning
confidence: 64%